Analysis of the right to live in a clean and healthy environment under Vietnamese law and suggestions on how it could be improved - Tran Cong Thiet (Studia Prawnicze KUL)
In October 2021, in line with previous international treaty obligations, in particular the 1972 Stockholm Declaration, the United Nations Human Rights Council’s Resolution 48/13, granted all people the right to live in a clean and healthy environment. Article 43 of the Vietnam Constitution affirms that a clean, healthy, and sustainable environment is a human right for all, not just a privilege for some. Nevertheless, environmental pollution and its devastating impact on local communities throughout Vietnam still generally continue unabated due to the failure of national and local authorities to adequately monitor polluters, enforce environmental protections, and prosecute offenders. The purpose of this article is to outline some of the reasons why problems exist in the implementation of current Vietnamese environmental law and provide some suggestions on how many of these challenges could be overcome.